SsCyp86 modulates Sporisorium scitamineum mating/filamentation and pathogenicity through regulating fatty acid metabolism - Cai, Enping; Deng, Jiaru; Feng, Ruqing; Zheng, Wenqiang; Wang, Yifang; Yan, Meixin; Chang, Changqing (Virulence, 2024)
Fatty acid metabolism constitutes a significant and intricate biochemical process within microorganisms. Cytochrome P450 (CYP450) enzymes are found in most organisms and occupy a pivotal position in the metabolism of fatty acids. However, the role of CYP450 enzyme mediated fatty acid metabolism in the pathogenicity of pathogenic fungi remains unclear. In this study, a CYP450 enzyme-encoding gene, , was identified in the sugarcane smut fungus and its functions were characterized using a target gene homologous recombination strategy and metabonomics. We found that the expression of was induced by or sugarcane wax or under the condition of mating/filamentation. Sexual reproduction assay demonstrated that the deletion mutant was defective in mating/filamentation and significantly reduced its pathogenicity. Further fatty acid metabolomic analysis unravelled the levels of fatty acid metabolites were reduced in the deletion mutant. Exogenous addition of fatty acid metabolites cis-11-eicosenoic acid (C20:1N9), pentadecanoic acid (C15:0), and linolenic acid (C18:3N3) partially restored the mating/filamentation ability of the deletion mutant and restored the transcriptional level of the , a pheromone response transcription factor that is typically down-regulated in the absence of . Moreover, the constitutive expression of in the deletion mutant restored its mating/filamentation. Our results indicated that SsCyp86 modulates the transcription by fatty acid metabolism, and thereby regulate the sexual reproduction of . These findings provide insights into how CYPs regulate sexual reproduction in .